The Calculus of Variations and Functional Analysis : With Optimal Control and Applications in Mechanics - Lebedev, Leonid P. ((Series on Stability, Vibration and Control of Systems. Series A ;)
Contenido: Cálculo básico de variaciones; Elementos de teoría del control óptima; Análisis Funcional; Algunas aplicaciones en mecánica.